'Richly Imaginative Barbarism': Stuart Hampshire and the Normality of Conflict. Issue 160 (1st September 2019) - Edyvane, Derek
Abstract : By way of an engagement with the thought of Stuart Hampshire and his account of the 'normality of conflict', this article articulates a novel distinction between two models of value pluralism. The first model identifies social and political conflict as the consequence of pluralism, whereas the second identifies pluralism as the consequence of social and political conflict. Failure to recognise this distinction leads to confusion about the implications of value pluralism for contemporary public ethics. The article illustrates this by considering the case of toleration. It contends that Hampshire's model of pluralism offers a new perspective on the problem of toleration and illuminates a new way of thinking about the accommodation of diversity as 'civility within conflict'.